Efficacy of rituximab as second-line therapy for autoimmune encephalitis: A systematic review and meta-analysis - Lin-ming Zhang; Xuan-lin Xing; Bing-ran Zhang; Qiu-juan Zhang; Yan-lin Zhu; Shu-ji Gao; Ming-wei Liu (Heliyon)
Background: Approximately 20%–50 % of individuals with autoimmune encephalitis (AE) demonstrate suboptimal responses to first-line therapies, leading to persistent neurological deficits and the need for second-line interventions. Although rituximab has shown potential as an alternative treatment in AE, the existing evidence remains insufficient. This study systematically evaluated and meta-analyzed the efficacy of rituximab in AE patients who either failed or exhibited inadequate responses to first-line treatments, aiming to refine and optimize therapeutic strategies for AE. Methods: A comprehensive search of PubMed, Embase, and the Cochrane Library databases was conducted, covering studies published up to June 10, 2024. In addition, manual cross-referencing of relevant studies was performed using both subject-specific and free-text terms such as “Rituximab,” “Rituxan,” “Mabthera,” “RTX,” “Mab,” “Ma,” “AE,” “encephalitis,” “Anti-NMDAR encephalitis,” and “autoimmune encephalitis.” Data on rituximab's efficacy as a second-line therapy in AE were independently screened and extracted by two researchers. Statistical analyses were conducted using R4.2.1 software to assess the pooled outcomes of the included studies. Results: Analysis of 14 studies involving 277 AE cases revealed an 80 % favorable prognosis rate (0.72–0.89) for rituximab, with superior efficacy in patients under 18 years compared to those over 18 (I2 = 65.9 %, 38.7%–81.0 %; p < 0.01). The prognosis rate for patients under 18 was 0.85 (0.76–0.93), while for those over 18, it was 0.72 (0.56–0.88). Furthermore, a disease duration of ≤180 days correlated with a better prognosis than durations exceeding 180 days, with rates of 0.82 (0.69–0.94) and 0.74 (0.61–0.87), respectively. Conclusion: Rituximab demonstrates an 80 % favorable prognosis rate in AE cases unresponsive to first-line treatments, particularly in patients under 18 or those with disease duration ≤180 days.